Integrasi Big Data dan AI untuk Pengambilan Keputusan dalam Smart City - T. Irfan Fajri; Novi Rahayu; Handry Eldo; Giatika Chrisnawati; Rizkia Shaulita (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This research explores the integration of Big Data technology and Artificial Intelligence (AI) in decision-making in the context of Smart City. With the massive growth of data from various sources such as IoT, sensors, and information systems, Big Data is becoming an important foundation for in-depth analysis. Meanwhile, AI provides the ability to process data in real-time, identify patterns, and generate accurate recommendations. This research aims to analyze how the combination of these two technologies can improve efficiency, sustainability, and quality of life in cities. The methods used include literature review and case analysis in several smart cities. The results show that the integration of Big Data and AI can support faster, more precise, and data-driven decision-making, thus encouraging the creation of a smarter and more responsive city.